2015
DOI: 10.4321/s1578-84232015000300016
|View full text |Cite
|
Sign up to set email alerts
|

Efectos del entrenamiento en la habilidad para repetir sprints (RSA) en arbitros de baloncesto

Abstract: Efectos del entrenamiento en la habilidad para repetir sprints (RSA) en arbitros de baloncesto Training effects in repeated sprint ability (RSA) in basketball referees Efeitos do treino na capacidade de repetir sprints (RSA) em árbitros de basquetebol P. Bayón, A. Vaquera, J.V. García-Tormo y R. Dehesa Departamento de Educación Física y Deportiva. Facultad de Ciencias de la Actividad Física y del Deporte. Universidad de León.Resumen: La mayor parte de los estudios en baloncesto se han centrado en el estudio de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Finally, regarding anthropometric measurements (i.e., body mass and body fat percentage), we did not observe apparent effects of training on our sample. These findings align with other research involving sub-elite male basketball referees [ 17 ], which found no significant differences in anthropometric metrics following a 5-week specific training intervention. However, it’s crucial to interpret these results cautiously as we did not control dietary intake, which could impact body mass or body fat percentage.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Finally, regarding anthropometric measurements (i.e., body mass and body fat percentage), we did not observe apparent effects of training on our sample. These findings align with other research involving sub-elite male basketball referees [ 17 ], which found no significant differences in anthropometric metrics following a 5-week specific training intervention. However, it’s crucial to interpret these results cautiously as we did not control dietary intake, which could impact body mass or body fat percentage.…”
Section: Discussionsupporting
confidence: 91%
“…Both training interventions resulted in improved RSA mean , aligning with earlier findings in sub-elite male basketball referees by Bayon et al [ 17 ], who conducted five weeks of specific physical training. Following their intervention, these authors noted a 5.3% increase in RSA mean for the experimental group, reporting significant differences favoring the experimental group over the control.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations